Efektivitas Pelaksanaan Tugas Balai Harta Peninggalan dalam Pengurusan Harta Peninggalan Berdasarkan KUHPerdata - Jeremia Manalu; Besty Habeahan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Heritage Center (BHP) is a government institution under the Ministry of Law and Human Rights of the Republic of Indonesia that has a strategic role in civil law, especially related to the management of heritage property. Rooted in colonial regulations and regulated in the Civil Code, BHP is authorized to represent and protect the legal interests of individuals whose whereabouts are unknown, immature, or legally incompetent. This study aims to analyze the implementation of BHP's duties in managing heritage assets based on the provisions of the Civil Code and identify supporting and inhibiting factors for its implementation. The method used is normative legal research with a legislative approach and literature study. The results of the study show that BHP's position is as a subject of public law that carries out private legal functions. BHP's authority includes the management of unmanaged legacies, acting as a guardian or guardian, and acting as a curator in bankruptcy cases. Despite having a strong legal basis, the effectiveness of the implementation of BHP's duties in the field has not been optimal. The obstacles faced include limited resources, lack of public understanding, and coordination between agencies that has not been maximized. Therefore, systematic improvement efforts are needed through institutional capacity building, legal socialization, and strengthening regulations and cross-sector synergy to support the effective and sustainable implementation of BHP's tasks.